Cultural Memory in Protohistoric and Ancient Mediterranean Societies: An historiographical introduction - Machuca Prieto, Francisco; Gomes, Francisco (My University, 2022)
Memory and its uses are not neutral. As noted by authors such as M. Halbwachs and J. Assmann, memory, in collective terms, is a powerful tool for identity building, and has been so since the dawn of Humanity. Within each particular society, the performative construction of collective memory consolidates a shared interpretation of what happened or what is worth remembering. This idea has made significant headway in archaeological research in the last three decades, as illustrated by a growing number of works dealing with memory in Prehistory and the Ancient world. However, the different languages and vocabularies on this topic may confuse those who approach this field, so a necessary first step is to summarize the meanings ascribed to terms like “collective”, “social” and “cultural memory”. Of these three concepts, the latter, put forward by J. Assmann, has undoubtedly had the greatest impact. In his view, “cultural memory” is nothing other than the remembrance of the past from shifting perspectives in the present. This phenomenon of production, reproduction, and transformation of narratives about a collective past was already common during the European Iron Age and Antiquity. Studies such as those by E. Bickerman on the Greek world, and, more recently, R. Golosetti on Pre-Roman Gaul, F. Marco Simón on Pre-Roman Iberia or K. Galinsky and K. Lapatin on the Roman world have made this clear. From a combination of literary, iconographic, and archaeological sources, the approaches of these authors to “cultural memory” confirm not only that remembering is an act of creation of meaning in the present through the past, but also that the exploration of the ways in which narratives about the past were built and deployed as part of broader processes of identity construction is a field of study which still holds great potential.
Keywords: Memoria colectiva; Memoria; Identidad; Paisaje; Edad del Hierro; Antigüedad